Almond-shell-derived Fe-La biochar enables magnetic capture and pyrolysis-assisted conversion of nanoplastics - Jin Ge; Zhaoshuang Li; Xu Xu; He Liu; Guoen Yang; Chuntao Kuang; Min Zhang; Zhenfei Yang; Yuanfeng Wei; Yiqiang Wu (Bioresource Technology, 2026)

Rutin attenuates liver fibrosis via the IRG1-itaconate-Nrf2 axis - Ningman Jiang; Jiao Zhang; Ge Kuang; Guohao Liu; Jingyuan Wan; Bin Wang; Zizuo Zhao (Inflammation Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Environmental impacts of sucralose in E-Cigarette aerosols: Degradation and toxicology - Wenwu Yang; He Chen; Liping Kuang; Ge Nie (Next Research, 2026)

Enhancement of selective lithium extraction from α-spodumene by autoclaving with NaOH and NaAlO2 at 200–300 °C - Shuhao Dong; Yakai Yang; Hao Zhang; Meiyan Yu; Hui Guo; Ge Kuang; Haidong Wang; Xiaohui Fan (Hydrometallurgy, 2026)

Trophic attenuation and transmission of antibiotic resistance in the aquatic food webs - Xue Xue; Shulun Jiang; You Ge; Yongjin Chen; Dongfa Gao; Long Ren; Zhen Kuang (Journal of Hazardous Materials, 2025)

Engineering fast-response thermal control for dynamic gene expression design in Halomonas - Jian-Lian Wu; Ya-Ge Xiao; Bao-Wen Liu; Ling-Fan Tian; Ling-Fei Tian; Yu-Xi Li; Jia-Wen Peng; Hai-Fan Zhu; You-Yang Wang; Zhe-Yi Kuang; Jiang-Jie Tian; Shuai Zheng; et al. (Chemical Engineering Journal, 2025)

Flash roasting for phase transformation of α-spodumene coupled with sulfuric acid pressure leaching to enhance lithium extraction - Dongqi Song; Wei Chen; Qingkang Yan; Yu Liu; Ge Kuang; Hui Guo; Guosheng Li; Yijun Cao (Minerals Engineering, 2025)

Bimetallic copper-bismuth microtubular electrodes with tunable interfaces for efficient electrochemical reduction of CO2 to formate - Beibei Ma; Hesamoddin Rabiee; Guoliang Chen; Yizhu Kuang; Tianjiu Zhu; Penghui Yan; Lei Ge; Zhonghua Zhu (Chemical Engineering Journal, 2025)

Integrating genome assembly, structural variation map construction and GWAS reveal the impact of SVs on agronomic traits of Brassica napus - Nian Wang; Xianshuai Song; Lieqiong Kuang; Ze Tian; Kaifeng Wang; Keqi Li; Lan Ge; Yu Wu; Xinfa Wang; Xiaoling Dun; Hanzhong Wang (Theoretical and Applied Genetics, 2025)

Two undescribed coumarins from Hansenia weberbaueriana - Yixiao Pan; Mengdan Liu; Yunjie Hu; Chenyi Yan; Dale Guo; Ge Kuang (Natural Product Research, 2025)

Study of natto extract for the amelioration of dinitrochlorobenzene-induced atopic dermatitis by integrating untargeted metabolomics, network pharmacology, and molecular simulation - Jin Wang; Liwen Zhang; Zhelin Kuang; Ye Ge; Yingqing Zhang (Food Bioscience, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

Monitoring slope stabilization of a reactivated landslide in the Three Gorges Reservoir Region (China) with multi-source satellite SAR and optical datasets - Jianming Kuang; Linlin Ge; Alex Hay-Man Ng; Stuart R. Clark; Sadra Karimzadeh; Masashi Matsuoka; Zheyuan Du; Qi Zhang (Landslides, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Hollow fiber gas-diffusion electrodes with tailored crystal facets for tuning syngas production in electrochemical CO2 reduction - Guoliang Chen; Lei Ge; Yizhu Kuang; Hesamoddin Rabiee; Beibei Ma; Fatereh Dorosti; Ashok Kumar Nanjundan; Zhonghua Zhu; Hao Wang (Chemical Engineering Journal, 2024)

Ecological responses and functional significance of paddy crust in the southern Chinese environment - Xiaolin Kuang; Yiyi Hu; Shaoning Chen; Yili Ge; Yiling Hu; Huijuan Song; Ke Song; Liang Peng (Environmental Pollution, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Primary sources of HONO vary during the daytime: Insights based on a field campaign - Dongyang Chen; Li Zhou; Song Liu; Chaofan Lian; Weigang Wang; Hefan Liu; Chunyuan Li; Yuelin Liu; Lan Luo; Kuang Xiao; Yong Chen; Yang Qiu; et al. (Science of The Total Environment, 2023)

Establishing essentially symmetrical combustion plus apparent improvement in burnout and NO emissions within a down-fired furnace by rearranging its W-shaped flame into a sidewall-dominated pattern - Yangyang Chen; Min Kuang; Zehao Ge; Yiping Zhao; Jiaqi Chen (Fuel, 2023)

An efficient method for undifferenced BDS-2/BDS-3 high-rate clock estimation - Xinyun Cao; Kaifa Kuang; Yulong Ge; Fei Shen; Shoujian Zhang; Jiancheng Li (GPS Solutions, 2022)

Phytoplankton Species Diversity Patterns and Associated Driving Factors in China’s Jiulong River Estuary: Roles That Nutrients and Nutrient Ratios Play - Feiyang Ge; Zhiyuan Ma; Bin Chen; Yu Wang; Xiaoqian Lu; Shenqun An; Dian Zhang; Wanting Zhang; Weiwei Yu; Wenxuan Han; Xingguang Yu; Zhenghua Liu; et al. (Frontiers in Marine Science, 2022)
Understanding diversity patterns and associated driving factors are the critical topics in macroecology and conservation biology. Phytoplankton are highly susceptible to environmental changes in estuaries, particularly eutrophication. This study examined phytoplankton alpha and beta diversity using investigation data in May (springtime), August (summer) and November (autumn) 2009 in China’s Jiulong River estuary, where it was easily polluted because of considerable discharge from a highly dense human population and low self-purification capacity with its limited river basin area, potentially resulting in eutrophication and then influencing phytoplankton diversity. Potential influencing factors were also explored, including dissolved oxygen, salinity, nutrients, nutrient ratios, geographic and hydrologic distance, and so on. The results indicated that Shannon’s index ( H’ ) and Pielou’s index ( J ) decreased from the estuary’s upper to middle and then increased from middle to lower reaches, Simpson’s ( D ) observed the opposite trend and species number ( S ) gradually increased from the estuary’s upper to lower reaches. For beta diversity, all the indices showed a gradual decrease trend from the estuary’s upper to lower reaches, where also, turnover dominated beta diversity for all seasons. It is noteworthy that the significant roles that nutrients and nutrient ratios played in shaping phytoplankton diversity patterns and the nutrient balance were characterized by excess nitrogen (N) and silicon (Si) and limited phosphorus (P), which could potentially cause diatom blooms. Findings also showed that decreasing Si concentrations can help to reduce overall pollution levels as well as the restoration of the estuary’s ecosystem better than just reducing N alone. Accordingly, this study advocates for the protection of the entire estuary system with particular emphasis on its upper reaches. Moreover, greater attention should also be paid to impacts associated with N input and nutrient ratio trade-offs to the prospective watershed management of this estuary. This study provides a practical approach to explore estuarine diversity in a comprehensive way, which can inform effective biodiversity conservation and also be applied to other marine ecosystems to better guide sustainable management and conservation practices.

Metformin prevents against oxidative stress-induced senescence in human periodontal ligament cells - Yunchun Kuang; Bo Hu; Ge Feng; Mingli Xiang; Yuejia Deng; Minmin Tan; Jie Li; Jinlin Song (Biogerontology, 2020)

Correlation between shear strength and soil physicochemical properties of different weathering profiles of the non-eroded and collapsing gully soils in southern China - Bifei Huang; Ming Qiu; Jinshi Lin; Jialin Chen; Fangshi Jiang; Ming-kuang Wang; Hongli Ge; Yanhe Huang (Journal of Soils and Sediments, 2019)

Coseismic deformation and source model of the 12 November 2017 M W 7.3 Kermanshah Earthquake (Iran–Iraq border) investigated through DInSAR measurements - Jianming Kuang; Linlin Ge; Graciela Isabel Metternicht; Alex Hay-Man Ng; Hua Wang; Mehdi Zare; Farnaz Kamranzad (International Journal of Remote Sensing, 2019)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

Nutrient removal by Chlorella vulgaris F1068 under cetyltrimethyl ammonium bromide induced hormesis - Qiongzhi Zhou; Feng Li; Fei Ge; Na Liu; Yangduo Kuang (Environmental Science and Pollution Research, 2016)

Three new sulphur glycosides from the seeds of Descurainia sophia - Wei-sheng Feng; Chun-Ge Li; Xiao-Ke Zheng; Ling-Ling Li; Wen-Jing Chen; Yan-Li Zhang; Yan-Gang Cao; Jian-Hong Gong; Hai-Xue Kuang (Natural Product Research, 2016)

Overexpression of SmLEA enhances salt and drought tolerance in Escherichia coli and Salvia miltiorrhiza - Yucui Wu; Congling Liu; Jing Kuang; Qian Ge; Yuan Zhang; Zhezhi Wang (Protoplasma, 2014)